STRATEGI ALTERNATIF PENETAPAN HARGA DENGAN PENDEKATAN DISKRIMINASI HARGA UNTUK MENINGKATKAN VOLUME PENJUALAN CAFÉ SEMANIS KAMU - Tetty Herawaty; Lina Auliana; Yolanda Oktavia; Cecep Safa’atul Barkah (Jurnal Bisnis Terapan, 2021)
This research was conducted at Café Semanis Kamu which aims to find out the right alternative strategy used to increase sales volume. This research was conducted with a descriptive qualitative method with sources of information obtained by interviews and literature study. The data analysis method uses an approach Internal Resources Based Analysis, VRIN Analysis (Valuable, Rare, Imitability, Non-Substitution), Sustainable Competitive Advantage (SCA) Analysis, and TOWS (Threats, Opportunities, Weakness, Strengths) Analysis. The results of data processing with this approach formed a price discrimination strategy with two program proposals, namely making package & reservation catalogs, and making special discounts.